Eosinophil Purification from Peripheral Blood - Akuthota, Praveen (2014)
Eosinophils are granulocytes integral to allergic inflammation and parasitic responses and comprise 1–4% of the circulating leukocytes in human beings under normal conditions. Isolation of human eosinophils allows for ex vivo and in vitro experimentation, providing a valuable tool for the study of allergic mechanisms. Here, we describe a technique for the isolation of human eosinophils by negative selection from whole blood obtained by venipuncture.